Loranthus pulverulentus: A Potent Source of Natural Antioxidants and Alternative Medicine. (29th October 2013) - Raza, Muhammad Asam; Kausar, Rukhsana; Rana, Faraz Ali; Danish, Muhammad; Shahwar, Durre; Anwar, Farwa
Abstract : This study was designed to evaluate the antioxidant potential of Loranthus pulverulentus . Stem bark, leaves, and seeds of Loranthus pulverulentus were extracted in methanol:water (90 : 10) and partitioned with n-hexane, chloroform, ethyl acetate, and n-butanol successively using partition chromatography. Total phenolic contents and antioxidant potential were checked using standard protocols. Total phenolic contents of all extracts were determined, using Folin–Ciocalteu reagent, and ranged between 151 ± 2.1 and 396 ± 1.6 for stem bark, 137 ± 0.9 and 430 ± 2.2 for, and 39 ± 0.6 and 231 ± 1.7 for seeds. The antioxidant potential of extracts was evaluated; namely, DPPH, FRAP, and total antioxidant models. The ethyl acetate extract of stem-bark, leaves, and seeds showed the highest activity in DPPH (94.5 ± 2.1%, 96.30 ± 0.9%, and 92.30 ± 1.1%, IC50 15.9 ± 0.5  μ g, 14.5 ± 0.8, and 102.7 ± 1.3, resp.), FRAP (7.7 ± 0.6, 7.5 ± 0.7 and 6.6 ± 0.7, resp.), and total antioxidant (0.95 ± 0.09, 1.19 ± 0.09, and 0.686 ± 0.08, resp.). Strong correlations were observed between total phenols versus total antioxidant activity, DPPH, and FRAP with R 2 values ranging from 0.8185 to 0.9951 (stem-bark), 0.6728 to 0.8648 (leaves), and 0.8658 to 0.9910 (seed) which indicated that phenolic contents are the major constituents responsible for antioxidant activity.